An Introduction To Character Education For Early ChildhoodThrough Music Instruments In Wayang Golek Reyog Ponorogo - Sulton .; Betty Yulia Wulansari; Prihma Sinta Utami (Universitas Muhammadiyah Ponorogo, 2020)
The Indonesian nation has experienced a decline in patriotism for the country. According to Sulton et al. (2020: 299)1, foreign cultures coming with access 5.0 very quickly affect the younger generation. People are starting to leave traditional art as a cultural heritage. One of them is the lack of socialization of musical instruments accompanying Reyog Ponorogo. Efforts to socialize patriotism can start from an early age. This is because early childhood is in the golden age where all information provided can be received easily. In this research, the instrument that was introduced to introduce Cinta Tanah Air character education in PAUD was the Reyog Ponorogo musical instrument used to accompany the Wayang Golek (Rod Puppet) Reyog Ponorogo art performance. The musical instruments, according to Mr. Shodiq Pristiwanto, S.Sn (2020) as Chairman III of Reyog Ponorogo Foundation, include kempul, trumpet, angklung, kendang, seven kenong as the identity of Wayang Golek Reyog Ponorogo music accompaniment. This research aimed to introduce Wayang Golek Reyog Ponorogo Musical Instrument since early childhood. This research method used a qualitative research with data collection using interviews. The results of this research show Wayang Golek Reyog Ponorogo can be used to introduce patriotism since earlychildhood .